Guidance on the assessment of the safety of feed additives for the target species - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Guido Rychen; Gabriele Aquilina; Giovanna Azimonti; Vasileios Bampidis; Maria de Lourdes Bastos; Georges Bories; Andrew Chesson; Pier Sandro Cocconcelli; Gerhard Flachowsky; Jürgen Gropp; Boris Kolar; et al. (EFSA Journal, 2017)
Draft Endorsed by the FEEDAP Panel 22 March 2017 Submitted for public consultation 6 April 2017 End of public consultation 31 May 2017 Adoption by the FEEDAP Panel 26 September 2017 Entry into force 1 May 2018 Abstract This guidance document is intended to assist the applicant in the preparation and the presentation of an application, as foreseen in Article 7.6 of Regulation (EC) No 1831/2003, for the authorisation of additives for use in animal nutrition. It specifically covers the assessment of the safety for the target species.